Semantics, logics, and calculi : essays dedicated to Hanne Riis Nielson and Flemming Nielson on the occasion of their 60th birthdays /: essays dedicated to Hanne Riis Nielson and Flemming Nielson on the occasion of their 60th birthdays. (2016) - Unknown
No abstract available